Makna Tema Masa Muda dalam MV “Cheers to Youth” SEVENTEEN: Analisis Semiotika Roland Barthes - Safina Raudhotunnisa (Prisani Cendekia Institute, 2026)
This study aims to analyze the meaning of the theme of youth in SEVENTEEN's music video,